Influence of TiO2 Nanoparticles on Growth and Phenolic Compounds Production in Photosynthetic Microorganisms - Mattia Comotto; Alessandro Alberto Casazza; Bahar Aliakbarian; Valentina Caratto; Maurizio Ferretti; Patrizia Perego (The Scientific World Journal)
The influence of titanium dioxide nanoparticles (pure anatase and 15% N doped anatase) on the growth of Chlorella vulgaris, Haematococcus pluvialis, and Arthrospira platensis was investigated. Results showed that pure anatase can lead to a significant growth inhibition of C. vulgaris and A. platensis (17.0 and 74.1%, resp.), while for H. pluvialis the nanoparticles do not cause a significant inhibition. Since in these stress conditions photosynthetic microorganisms can produce antioxidant compounds in order to prevent cell damages, we evaluated the polyphenols content either inside the cells or released in the medium. Although results did not show a significant difference in C. vulgaris, the phenolic concentrations of two other microorganisms were statistically affected by the presence of titanium dioxide. In particular, 15% N doped anatase resulted in a higher production of extracellular antioxidant compounds, reaching the concentration of 65.2 and 68.0 mg gDB-1 for H. pluvialis and A. platensis, respectively.